Oxygen and trace elements (Mn/Ca ratio) collected in Anholt, Hano Bay and Gullmar fjord from Groeneveld et al., (2018) and Groeneveld and Filipsson (2013) - Ferraro, Mattia; Risebrobakken, Bjørg; Polovodova Asteman, Irina; Darelius, Elin; Tisserand, Amandine; Gallo, Natalya; Salvanes, Anne Gro Vea (In: Ferraro, M et al. (2025): Dissolved oxygen concentration, trace elements concentration, carbon isotope composition and foraminifera assemblages data from Western Norwegian fjords [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.982538, 2025)
Oxygen (umol/kg) and trace elements (Mn/Ca ratio) from Groeneveld et al., (2018) and Groeneveld and Filipsson (2013). We used oxygen of seawater to calculate oxygen saturation and the Apparent Oxygen Utilisation (AOU) using the gsw_O2sol toolkit for python.
Keywords: carbon isotope; Fjord; Foraminifera; Oxygen; proxy; trace elements